Odpowiedzi

Najlepsza Odpowiedź!
2010-01-27T17:21:04+01:00
A+(a-b) = a+a-b = 2a-b
2x-(x+4) = 2x-x-4 = x-4
7-(-x+4) = 7+x-4 = 3+x
-(x+4)+(x-5) = -x-4+x-5 = -9
1-(t+p)-(t-2) = 1-t-p-t+2 = 3-2t-p
-(-y+2)+(-2y-4) = y-2-2y-4 = -y-6
6(x-4)-2 = 6x-24-2 = 6x-26
2(x+1)-3(x-1) = 2x+2-3x+3 = -x+5
-3(y-2)+4(y+2) = -3y+6+4y+8 = y+14
5(x-y-1)-4(x+2) = 5x-5y-5-4x-8 = x-5y-13
2(3a+b)-2(a-b) = 6a+2b-2a+2b = 4a+4b
½(4x-4)-2x = 2x-2-2x = -2
x(x-1)-3(x²-x) = x²-x-3x²+3x = -2x²+2x
5a(a-3)-3a(a-5) = 5a²-15a-3a²+15a = 2a²
3x(x+⅓y)-2y(½x-½) = 3x²+y-xy+y = 3x²+2y-xy
3 3 3
2010-01-27T17:37:30+01:00
A+(a-b)=a+a-b=2a-b
2x-(x+4)=2x-x-4=x-4
7-(-x+4)=7+x-4=3+x
-(x+4)+(x-5)=-x-4+x-5=-9
1-(t+p)-(t-2)=1-t-p-t+2=3-2t-p
-(-y+2)+(-2y-4)=y-2-2y-4=-y-6
6(x-4)-2=6x-24-2==6x-26
2(x+1)-3(x-1)=2x+2-3x+3=-x+5
-3(y-2)+4(y+2)=-3y+6+4y+8=y+14
5(x-y-1)-4(x+2)=5x-5y-5-4x-8=x-5y-13
2(3a+b)-2(a-b)=6a+2b-2a+2b=4a+4b
½(4x-4)-2x=2x-2-2x=-2
x(x-1)-3(x²-x)=x²-x-3x²+3x=-2x²+2x
5a(a-3)-3a(a-5)=5a²-15a-3a²+5a=2a²
3x(x+⅓y)-2y(½x-½)=3x²+xy-xy+y=3x²+y
2 3 2